2013
DOI: 10.1111/adb.12106
|View full text |Cite
|
Sign up to set email alerts
|

Ibudilast reduces alcohol drinking in multiple animal models of alcohol dependence

Abstract: Neuroinflammatory signaling pathways in the CNS are of current interest as potential pharmacotherapy targets for alcohol dependence. In this study, we examined the ability of ibudilast, a non-selective phosphodiesterase inhibitor, to reduce alcohol drinking and relapse in alcohol-preferring P rats, high-alcohol drinking HAD1 rats, and in mice made dependent on alcohol through cycles of alcohol vapor exposure. When administered twice daily, ibudilast reduced alcohol drinking in rats by approximately 50% and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 20 publications
10
85
2
Order By: Relevance
“…Ibudilast is a phosphodiesterase inhibitor that suppresses pro-neuroinflammatory glial responses [16, 249]. In preclinical studies, minocycline and ibudilast have been shown to attenuate alcohol self-administration [250, 251], morphine-induced dopamine release in the nucleus accumbens [252], and morphine-conditioned place preference [253]. Recent studies have begun to investigate these medications in humans.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Ibudilast is a phosphodiesterase inhibitor that suppresses pro-neuroinflammatory glial responses [16, 249]. In preclinical studies, minocycline and ibudilast have been shown to attenuate alcohol self-administration [250, 251], morphine-induced dopamine release in the nucleus accumbens [252], and morphine-conditioned place preference [253]. Recent studies have begun to investigate these medications in humans.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…These include topiramate, which was originally used as an anticonvulsant drug used to treat epilepsy [131,132], naltrexone, an opiate receptor antagonist [133] and aripiprazole, an atypical antipsychotic, with potential for treating alcohol dependence [134]. And, rele vant to the current review and the role of the neuroimmune system in AUD, there is evidence that ibudilast, a nonselective phosphodiesterase inhibitor, decreases alcohol consumption in animal models [135].…”
Section: Drug Repurposingmentioning
confidence: 92%
“…Ibudilast, commonly used in the treatment of asthma, inhibits PDE activity and possesses anti-inflammatory and neuroprotective effects (Rolan et al, 2009). Systemic administration of ibudilast inhibits ethanol (Bell et al, 2015) and methamphetamine intake (Snider et al, 2013), sensitization of the locomotor response to methamphetamine (Snider et al, 2012), as well as stress-and drug-primed reinstatement of methamphetamine seeking (Beardsley et al, 2010). Ibudilast also reduces morphine withdrawal and CPP, likely as a result of its ability to reduce morphine-induced dopamine release in the NAc (Rolan et al, 2009;Schwarz and Bilbo, 2013).…”
Section: G Glial Modulatorsmentioning
confidence: 99%